Fluks Termal dalam Porous Media saat Mengkondensasi Uap - Siswanto, Eko (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
The aim of present study is to observe behavior of heat fluxes in porous media during it condenses the extracted-moist from a vapor related to its heat- and mass-transfer. This study applies two types of porous media which have difference in thermal conductivity, and it considers various ambient-temperatures. The test is conducted by streaming a laminar saturated vapor over porous glass-beads and alumina-balls media inside a duct, where the outside of the duct is treated by the ambient-temperatures. The vapor with various temperatures is forced tangentially over the upper-face of the media, whereas temperature of bottom of the media is kept to be constant. As for treat-I, the ambient temperatures are maintained at a constant value, hence, temperature ratio of the vapor to the ambient is non-unity. Furthermore, for treat-II, the ambient temperatures are increased with increasing the vapor temperatures such as the temperature ratio of the vapor to the ambient becomes unity. From this study, it can be informed that the heat fluxes on the porous media play a key role on condensing the extracted-moist. However, the gradual increase of the condensate inside the porous media decreases effective thermal conductivity on the bed of alumina balls and glass beads, and it further generates the un-steady heat transfer of the condensation.Keywords : heat fluxes, thermal conductivity, saturated vapor